Pengaruh Metode Field Trip Terhadap Keterampilan Menulis Cerpen Siswa Kelas IX MTS Hasan Yamani - Basri, Rahmaniar; Idawati, Idawati; Sakaria, Sakaria (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study aims to determine the effect of Field Trip method on short story writing skills of grade IX students of MTs Hasan Yamani. The type of research used in this study is pre-experimental design. The sample taken was one class, namely class IX C MTs Hasan Yamani consisting of 24 students. The research instrument used in this study was a short story writing test. The data collection technique used was a test technique to obtain data on the effect of the Field Trip method on the short story writing skills of class IX students of MTs Hasan Yamani. The test of student learning outcomes is in the form of a test which includes a pretest and posttest. Data analysis in this study used two techniques, namely descriptive statistics and inferential statistics. The results showed that the Field Trip method significantly affected the short story writing skills of ninth grade students of MTs Hasan Yamani. This is because the application of the Field Trip method is able to foster students' interest and creativity in writing short stories. Students' short story writing skills before and after applying the Field Trip method experienced a significant increase. This is evidenced from the average student score before using the Field Trip method in learning to write short stories, which is 71.13 and after using the Field Trip method which is 80.17.